Glymphatic system dysfunction in patients with cluster headache. Issue 6 (17th May 2022) - Kim, Jinseung; Lee, Dong Ah; Lee, Ho‐Joon; Park, Bong Soo; Ko, Junghae; Park, Si Hyung; Lee, Yoo Jin; Kim, Il Hwan; Park, Jin Han; Park, Kang Min
Abstract: Introduction: The aim of this study was to investigate alterations of the glymphatic system function in patients with cluster headache. Methods: We enrolled patients with cluster headache and healthy controls, and they underwent brain magnetic resonance imaging (MRI), including diffusion tensor imaging (DTI). We used the MRIcron and DSI studio programs for DTI preprocessing and DTI analysis with perivascular space (DTI‐ALPS) index calculation. Results: Fourteen patients with cluster headache and 23 healthy controls were enrolled. The DTI‐ALPS indexes of the groups were significantly different. The DTI‐ALPS index for the patients with cluster headache was lower than that for the healthy controls (1.586 vs. 1.786, p = 0.044). There was a significant negative correlation between the DTI‐ALPS index and age in the patients with cluster headache ( r = −0.549, p = 0.042). However, the DTI‐ALPS index was not associated with other clinical characteristics, including disease duration and headache intensity ( r = −0.405, p = 0.150; r = −0.048, p = 0.869, respectively). Conclusion: Patients with cluster headache had a lower DTI‐ALPS index than the healthy controls; this might indicate glymphatic system dysfunction in the patients with cluster headache. Further research is required to determine whether glymphatic system dysfunction is related to the pathophysiology of cluster headache. Abstract : This study investigated the alterations of the glymphatic system function associated with cluster headaches. Patients with cluster headaches had a lower DTI‐ALPS index than the healthy controls. It provides insights for further research into the association between glymphatic system dysfunction and cluster headaches and the evidence of this association will guide interventions for cluster headaches and improve patient outcomes.